Simultaneous removal of COD, nitrogen and phosphorus and the tridimensional microbial response in a sequencing batch biofilm reactor: with varying C/N/P ratios - Chao, Chunfang; Zhao, Yingxin; Keskar, Jayant; Ji, Min; Wang, Zijian; Li, Xin (Biochemical engineering journal, 2020)
[Display omitted] •Simultaneous nutrients removal in SBBRs were evaluated at varying C/N/P ratios.•Lower C/N/P inhibited S-SBBR more severely in terms of TP removal.•Both the microbial diversity and richness were effected by C/N/P ratios.•Microorganism in suspended sludge and biofilm showed different characteristics.•PAOs and DNPAOs enriched at the C/N/P of 33.3:8.3:1. Two lab-scale sequencing batch biofilm reactors with no salt (N-SBBR) and 10.0 g/L salt (S-SBBR) were operated to explore the simultaneous COD, nitrogen, phosphorus removal behavior and the microbial diversity as well as tridimensional (suspended sludge, exterior biofilm and interior biofilm) key functional microbial groups responses to varying C/N/P ratios from 125:8.3:1 to 33.3:8.3:1. The simultaneous nitrification and denitrification process and denitrifying phosphorus removal process were observed in this SBBR system. The N-SBBR showed better adaptation to low C/N/P (33.3:8.3:1), compared with the performance in S-SBBR, removal efficiency of ammonia nitrogen and phosphorus in N-SBBR showed 15% and 30% enhancement. The sludge samples from N-SBBR collected at the C/N/P ratio of 70.0:7.0:1 had the highest bacterial richness and diversity. The abundance of bacterial in suspended sludge, exterior biofilm and interior biofilm were different, the interior biofilm tends to favour the growth of denitrifying phosphorus bacteria (Pseudorhodobacter) indicating the complicated nitrogen and phosphorus removal processes.